Review paperHerpes simplex virus vaccines in prophylaxis and treatment - Szramka, Beata; Kowalczyk, Michał J.; Żaba, Ryszard (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2008)
In the article general information concerning the Herpes simplex (HSV) virus is discussed, with particular attention to strategies of preparing an effective vaccine against this pathogen. HSV induces herpes within the mucous membranes of the genitals and regions of the oral cavity, lips and eyes. It is worth remembering that genital herpes is the most frequent sexually transmitted disease and is becoming an increasingly significant problem in social, health and economic dimensions. At present acyclovir is administered in curing herpes; it demonstrates great effectiveness and safety of taking, but is not counteracting the spread of the virus in the population. A potent vaccine would create a chance of stopping the process. There have been many attempts to develop one, which unfortunately, so far, have ended up with failures in clinical trials. New vaccine strategies, using the newest tools of molecular biology, give hope that soon the aim will be achieved.